Construction of a flocculent saccharomyces cerevisiae fermenting lactose - Domingues, Lucília (1999)
A flocculent Saccharomyces cerevisiae strain with the ability to express both the LAC4 (coding for b-galactosidase) and LAC12 (coding for lactose permease) genes of Kluyveromyces marxianus was constructed. This recombinant strain is not only able to grow on lactose, but it can also ferment this substrate. To our knowledge this is the first time that a recombinant S. cervisiae has been found to ferment lactose in a way comparable to that of the existing lactose-fermenting yeast strains. Moreover, the flocculating capacity of the strain used in this work gives the process several advantages. On the one hand, it allows for operation in a continuous mode at high cell concentration, thus increasing the system's overall productivity; on the other hand, the biomass concentration in the effluent is reduced, thus decreasing product separation/purification costs.